2019
DOI: 10.3390/su11143838
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Simulation Model for the Optimization of the Taxi Management System

Abstract: The paper presents a simplified simulation model of the operation of a taxi system. The model retains the main features of a real taxi transportation system and despite its simplicity examines the system behavior in different conditions. It was shown that for every request generation rate a critical number of taxis in disposal could be determined. If the real number of taxis is lower than the critical number, the queue of pending requests grows in an unlimited way. On the other hand, if the real number of taxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The need for mobility is constantly increasing as the resources are limited. In such a situation it is important to maximize the use of resources (Król & Król, 2019). This also refers to taxi management systems, which are an integral part of the modern city's sustainable transport infrastructure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for mobility is constantly increasing as the resources are limited. In such a situation it is important to maximize the use of resources (Król & Król, 2019). This also refers to taxi management systems, which are an integral part of the modern city's sustainable transport infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for any taxi company, the issue of deciding an appropriate number of taxis at disposal seems to be crucial. This arises an innate trade-off between the passengers waiting for a taxi and the income earned (Król & Król, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis and confinement of photoactive species in zeolite pores have been reported in a quite high number of studies. In a recent article by GionCalzaferri and co-workers, it was found that the organic dye hostasol red (HR) could be incorporated into zeolite L (ZL) at ambient conditions and revealed strong absorption and luminescence in the 200-700 nm region, even though some variations have been observed in the optical property of the dye by changing the cationic nature of the zeolite (Devaux et al, 2014;Król, 2019). The results showed overall a positive response, in that the dye-zeolite hybrids obtained exhibit higher absorption and emission properties than the free dye, in the UV-visible spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In big cities and towns, people's mobility is constantly increasing, but the resources are limited, demanding to maximize the use of resources (Król & Król, 2019). Transportation is any medium through which we can reach from place to place.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for any taxi company, the issue of deciding an appropriate number of taxis in disposal seems to be crucial. It should be a trade-off between the passengers waiting for a taxi and the income earned (Król & Król, 2019).…”
Section: Introductionmentioning
confidence: 99%